Sexual Dysfunction Among Patients With Schizophrenia in Southwest Nigeria (2018)
Sexual functioning has received little attention as an important aspect of patient care for those suffering from schizophrenia. In Nigeria, cultural and religious factors often prevent patients from talking with their clinician about their sexual life. The aim of our study was to assess the frequency and nature of sexual dysfunction inpatients with schizophrenia and assess the determinants of sexual dysfunction in such patients. Sexual dysfunction was assessed with the Arizona Sexual Experience Scale in 90 patients with schizophrenia. Demographic and clinical characteristics including quality of life, the severity of schizophrenia, and perceived stigma were recorded using a standardized protocol and at a collection. The prevalence of sexual dysfunction was 36.7%. Higher scores on the negative subscale of the Positive and Negative Syndrome Scale (PANSS), the general subscale of the PANSS, the total scores on the PANSS, and a family history of mental illness were significantly associated with sexual dysfunction. The only significant predictor of sexual dysfunction was the severity of the negative subscale of the PANSS. This study highlights the high prevalence of sexual dysfunction among patients with schizophrenia. Efforts should be made to identify and address this problem.